(3GdgjFIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3Ydi Hf GdJQLeGf s)
(3ChdgG (B:s
(3GYde Gf GdYGde EfSGf cHjQ fYfi Hg GdSehGJ hGdCQV heG HjfgeG ef GdNdGFa CLeYjf s
(3BNQgG (B:s
(3hHYVgG dGJRGd HNVQJgG hhQbgG CjGe ehJgG hgPG cGa ajeG bUOJ Gdjg ef GdGNJUGQ ai Yde GdgjFI hGdGKGQ GdSeGhjI def GQGO GdTQhY ai gPG Gdaf GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG QShe hCTcGds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3Gdadcs